DIGITAL MAPS (GOOGLE MAPS, STORYMAPJS) IN THE TRAINING OF FUTURE HISTORY TEACHERS: OPPORTUNITIES FOR THE DEVELOPMENT OF SPATIAL COMPETENCE - RUDYANIN , Ivan (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2026)
The article is devoted to the study of the potential of using digital maps, in particular Google Maps and StoryMapJS, in the process of training future history teachers. The main attention is focused on the capabilities of these tools for the development of spatial competence of education seekers as one of the key professional qualities of a modern teacher. The purpose of the study is to analyze the theoretical and methodological principles of using modern digital cartographic services, in particular Google Maps and StoryMapJS, in the professional training of teachers and to determine their potential for the targeted development of spatial competence of education seekers. It is substantiated that the active use of digital maps not only deepens knowledge about historical space, but also develops the skills of spatial thinking, critical analysis of sources, interpretation of geospatial data and digital literacy, which are necessary for the effective work of a history teacher in the conditions of a modern educational environment. Scientific works on visualization, electronic educational resources and cartographic training were analyzed, and the need for a comprehensive study of the integration of these digital tools was identified. It is established that Google Maps (in particular, My Maps) is an indispensable tool for deep spatial analysis, landscape comparison and the creation of thematic layers, which contributes to the development of critical thinking about the geographical aspect of history. The StoryMapJS service is highlighted as a key tool for narrative cartography, which allows integrating multimedia content and creating exciting linear historical stories closely tied to geographical points, forming practical didactic skills. The implementation of an intensive practical module focused on project work (creation of a digital educational product) using the specified tools is proposed. Examples of project tasks on the history of Ukraine are given to develop spatial competence of education seekers. A multi-component approach to assessment is justified, which takes into account scientific reliability, methodological value, technical quality and individual contribution of each student. The findings confirm that the integrated use of Google Maps and StoryMapJS provides a systematic approach, increases cartographic literacy, and significantly enhances the motivation of future teachers, preparing them to create a modern interactive educational environment. Further research is needed to develop systematic methods for objectively measuring the growth of spatial competence.